Genetics of Substance Use Research and Clinical Aspects - Vanyukov, Michael M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book illuminates the complex problems in genetic studies of substance use and addiction. It provides a comprehensive overview that fills the gap in the literature and points out future directions. The book includes three sections that apply to any complex traits and disorders, particularly psychological and psychiatric. The first section covers the traits and phenotypes that are the target of genetic research in substance use and addiction. Following this, the second section analyzes the methods and results of biometric genetic studies in this area. The third section reviews research in gene mapping and epigenetics. Genetics of Substance Use is a first-of-its-kind monograph that presents contemporary solutions and methods for a wide range of researchers and practitioners across disciplines. .
S ubstance use phenotyping -- Substance use: disorders and continuous traits -- Neurobiological systems in substance use -- Psychological mechanisms of substance use -- Biometric genetic studies in substance use -- Twin studies -- Family and adoption studies -- Genomic studies in substance use -- Gene mapping in complex disorders -- Linkage and association studies -- Epigenomic studies -- Conclusions.
Keywords: Psychiatry; Medical genetics; Psychiatry; Medical Genetics; Substance-Related Disorders